Hierarchically three-dimensional ZrO2/Fe3O4/C nanocomposites with Janus structure for high-efficiency electromagnetic wave absorption - Xue, Ying; Liu, Xianyuan; Lu, Xianyong (Journal of materials science & technology, 2024)
Hierarchically three-dimensional (3D) materials present a pivotal challenge and opportunity in achieving effective microwave absorption with synergistic effects. In this work, α-Fe2O3@ZrO2 with core-shell structure were fabricated in-situ on aramid nanofibers by a solvothermal method. Following calcination, 3D ZrO2/Fe3O4/C nanocomposites with Janus structure have been successfully synthesized. By controlling the lattice match and mismatch in both processes, a core-shell structure of α-Fe2O3@ZrO2 and Janus structure of ZrO2/Fe3O4 have been well-define performed. The composite material ZrO2/Fe3O4/C-700 has a minimum reflection loss (RLmin) of −67.4 dB at a thickness of 2.0 mm. The effective absorption bandwidth (EAB) at a thickness of 2.4 mm is 6.0 GHz (11.0–17.0 GHz). This study provides a novel strategy for fabricating high-efficiency electromagnetic wave absorption materials with dual synergistic effects in nanosized scale.